Adaptive algorithm reallocation of network resources in a network that supports NFV tech-nology - Muhi-Aldeen, Hassan Mohamed; Tkachova, O.B. (Radiotekhnika, 2017)
The work is devoted to solving the problem of dynamic reallocation of network resources in multiservice networks with the NFV support to ensure an adequate quality of service. This objective is achieved through development of the adaptive network resource reallocation algorithm, the main criterion of which serves to minimize the final cost. Based on the results of mathematical modeling, an experiment was performed that allowed estimating the gain from using the developed algorithm.